(3QSGdI aj GdJOHjQ MjK dG jMVQ WHjHs - (3gHI Gddg Hf RjO Hf MSf Hf GaQGFje Hf jYbhH Hf LejY GdGSQGFjdj, GdeJWHH GdeUQj,J (B594 (3g` s
(3ChdgG (B:s
(3PcQJ CWGd HbGAc hCOGe JCjjOc eG JJNhag ef GdNHQI GdTOjOI hGdZdW GdaGOM ajeG jJOGhi Hg eJi YQV dc eQV ai ehVY jJYPQ Ydjc ajg hLO Cf WHjH s
(3BNQgG (B:s
(3Cffi CQOJ Cf jJVM YfOc hYfO YRc eeG YSi Cf JfaY Edjg gPg GdQSGdI hGdMeO ddg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdNGeSs
(3bhHdJ gPg GdfSNI hUMMJs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B72s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI jhJG s
Keywords: (3GdWHs